2011
DOI: 10.1371/journal.pgen.1002100
|View full text |Cite
|
Sign up to set email alerts
|

Two Evolutionary Histories in the Genome of Rice: the Roles of Domestication Genes

Abstract: Genealogical patterns in different genomic regions may be different due to the joint influence of gene flow and selection. The existence of two subspecies of cultivated rice provides a unique opportunity for analyzing these effects during domestication. We chose 66 accessions from the three rice taxa (about 22 each from Oryza sativa indica, O. sativa japonica, and O. rufipogon) for whole-genome sequencing. In the search for the signature of selection, we focus on low diversity regions (LDRs) shared by both cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
128
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(143 citation statements)
references
References 37 publications
10
128
0
4
Order By: Relevance
“…Despite the fact that rice is a major cereal and a model system for plant biology, the evolutionary origins and domestication processes of cultivated rice have long been debated. The puzzles about rice domestication include: (1) where the geographic origin of cultivated rice was, (2) which types of O. rufipogon served as its direct wild progenitor, and (3) whether the two subspecies of cultivated rice, indica and japonica, are derived from a single or multiple domestications.A wide range of genetic and archaeological studies have been carried out to examine the phylogenetic relationships of rice, and investigate the demographic history of rice domestication [10][11][12][13][14][15][16][17][18][19] . Molecular phylogenetic analyses indicated that indica and japonica originated independently 3,10,20 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that rice is a major cereal and a model system for plant biology, the evolutionary origins and domestication processes of cultivated rice have long been debated. The puzzles about rice domestication include: (1) where the geographic origin of cultivated rice was, (2) which types of O. rufipogon served as its direct wild progenitor, and (3) whether the two subspecies of cultivated rice, indica and japonica, are derived from a single or multiple domestications.A wide range of genetic and archaeological studies have been carried out to examine the phylogenetic relationships of rice, and investigate the demographic history of rice domestication [10][11][12][13][14][15][16][17][18][19] . Molecular phylogenetic analyses indicated that indica and japonica originated independently 3,10,20 .…”
mentioning
confidence: 99%
“…A wide range of genetic and archaeological studies have been carried out to examine the phylogenetic relationships of rice, and investigate the demographic history of rice domestication [10][11][12][13][14][15][16][17][18][19] . Molecular phylogenetic analyses indicated that indica and japonica originated independently 3,10,20 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, pooled next-generation sequencing (NGS) of multiple individuals from a population has gained in popularity (e.g., Turner et al 2010Turner et al , 2011He et al 2011;Kolaczkowski et al 2011;Boitard et al 2012;Fabian et al 2012;Kofler et al 2012;Lamichhaney et al 2012;Orozco-terWengel et al 2012), as it offers a cost-efficient alternative to sequencing of single individuals. However, estimating allele frequencies from read counts sequenced from a pool implies a second level of sampling variance (Futschik and Schlötterer 2010;Zhu et al 2012), which needs to be considered in population genetic analyses.…”
mentioning
confidence: 99%
“…Genetic studies remain divided as to whether rice domestication had a single origin or multiple origins (He et al 2011;Molina et al 2011;Sang and Ge 2007). The multiple-origins model proposes two centres of domestication, one in China ca.…”
Section: Origins Of Ricementioning
confidence: 99%